Current perspective in metal oxide based photocatalysts for virus disinfection: A review. (15th April 2022) - Soni, Vatika; Khosla, Atul; Singh, Pardeep; Nguyen, Van-Huy; Le, Quyet Van; Selvasembian, Rangabhashiyam; Hussain, Chaudhery Mustansar; Thakur, Sourbh; Raizada, Pankaj
Abstract: Nanotechnology holds huge potential for the prevention of various viral outbreaks that have increased at a disquieting rate over the past decades. Metal oxide nanomaterials with oxidative capability are the effective materials that provide platforms as well as tools for the well understanding of the mechanism, its detection, and treatment of various viral diseases like measles, influenza, herpes, ebola, current COVID-19 etc. In this inclusive review, we survey various previous research articles on different notable photoactive transition metal oxides that possess enough potential to act as antiviral agents for the deactivation of harmful viruses. We investigated and highlighted the plausible photocatalytic oxidative mechanism of photoactive transition metal oxides in degrading viral coatings, genomic RNA using suitable free radical generation. The key finding of the present review article including the discovery of a vision on the suitable photocatalytic transition metal oxides that have been proven to be excellent against harmful viruses and consequently combatting deadly CoV-2 in the environment. This review intends to provide conclusive remarks and a realistic outlook on other advanced photocatalytic metal oxides as a potential solution in battling other similar upcoming pandemics. Graphical abstract: Herein, the key finding of the present review article including the discovery of a vision on the suitable photocatalytic transition metal oxides that have been proven to be excellent against harmful viruses and consequently combatting deadly CoV-2 in the environment. Image 1 Highlights: Rapid spread of SARS-CoV-2 virus is a significant concern. Focuses on the significant roles of various transition metal oxides as antiviral agents. Significance of generated reactive oxygen species in virus inactivation process. The future prospective for virus disinfection were proposed.